Land management of reclaimed lands: current status and development prospects - Dorosh, Y.; Sakal, O.; Kharytonenko, R.; Derkulskyi, R. (Land Management, Cadastre and Land Monitoring, 2025)
In the context of sustainable development, climate change, and post-war recovery, this study addresses the challenges of land management for reclaimed (ameliorated) lands in Ukraine. It is substantiated that land reclamation, aligned with the concept of sustainable development, integrates economic, social, and environmental aspects over the long term for the benefit of current and future generations in agricultural land use. Effective approaches to integrated water and land resource management are examined, with an emphasis on employing modern land-monitoring technologies such as geographic information systems (GIS) and remote sensing. Open data on the status of reclaimed lands in Ukraine, including irrigation and drainage infrastructure, as well as their registration in accordance with existing legislation, are systematized. Improvements in legal norms on land management for reclaimed lands are proposed, taking into account the need to adapt reclamation systems to climate change. The importance of specialized land management projects is highlighted, as they account for the specific characteristics of reclaimed lands. Such projects will foster the practical implementation of integrated land and water resource management, ensuring land restoration and productivity gains, and contributing to the socio-economic and environmental objectives of agricultural land use. Particular attention is given to integrated land and water resource management aimed at restoring reclaimed areas in the post-war period by engaging local communities, investors, and government agencies. Implementing the proposed measures, aimed at climate change adaptation and mitigating its adverse effects, will also help combat land degradation and desertification, thereby expanding the acreage of productive agricultural land. Key words: reclaimed (ameliorated) lands, sustainable development, integrated land and water resource management, geographic information systems (GIS), land management (land use planning), climate change adaptation, irrigation systems, drainage systems, post-war recovery, infrastructure modernization, regulatory framework, socio-economic development, land management (land use) projects, organization of reclaimed lands